Lactate induces metabolic and epigenetic reprogramming of pro‐inflammatory Th17 cells. (10th October 2022) - Lopez Krol, Aleksandra; Nehring, Hannah P; Krause, Felix F; Wempe, Anne; Raifer, Hartmann; Nist, Andrea; Stiewe, Thorsten; Bertrams, Wilhelm; Schmeck, Bernd; Luu, Maik; Leister, Hanna; Chung, Ho‐Ryun; et al.
Abstract: Increased lactate levels in the tissue microenvironment are a well‐known feature of chronic inflammation. However, the role of lactate in regulating T cell function remains controversial. Here, we demonstrate that extracellular lactate predominantly induces deregulation of the Th17‐specific gene expression program by modulating the metabolic and epigenetic status of Th17 cells. Following lactate treatment, Th17 cells significantly reduced their IL‐17A production and upregulated Foxp3 expression through ROS‐driven IL‐2 secretion. Moreover, we observed increased levels of genome‐wide histone H3K18 lactylation, a recently described marker for active chromatin in macrophages, in lactate‐treated Th17 cells. In addition, we show that high lactate concentrations suppress Th17 pathogenicity during intestinal inflammation in mice. These results indicate that lactate is capable of reprogramming pro‐inflammatory T cell phenotypes into regulatory T cells. Synopsis: Lactate is a common metabolite in the tumor and inflammatory environment. High extracellular lactate concentrations promote the reprogramming of pro‐inflammatory Th17 cells towards regulatory T cell‐like phenotypes by metabolic and epigenetic mechanisms. Lactate, a co‐product of glycolysis, increases mitochondrial oxidative phosphorylation and ROS production in Th17 cells. ROS‐dependent IL‐2 signaling induces Foxp3 expression and suppresses the production of IL‐17A. Treatment of Th17 cells with extracellular lactate leads to an enrichment of H3K18 lactylation at the Foxp3 locus. Lactate promotes phenotypic switching of Th17 effector cells to regulatory T cells. Abstract : Lactate is a common metabolite in the tumor and inflammatory environment. High extracellular lactate concentrations promote the reprogramming of pro‐inflammatory Th17 cells towards regulatory T cell‐like phenotypes by metabolic and epigenetic mechanisms.